Enhancing Students’ Mathematical Conceptual Understanding through Team Games Tournament with a Culturally Responsive Teaching Approach - Amanah, Nabilla Nur; Alifiani, Alifiani; Novariana, Meilisa (Journal of Education and Learning Mathematics Research (JELMaR), 2025)
Abstract: This study uses the Teams Games Tournament (TGT) learning model and the Culturally Responsive Teaching (CRT) approach to enhance students’ understanding of mathematical concepts. Classroom action research is a study design conducted at SMP Negeri 20 Malang with 32 eighth-grade students as the subject group. The study consists of cycles of four stages: planning, action implementation, observation, and reflection. The instruments used are concept understanding tests, observation forms, and interview protocols. The average student score rose from 55.13 in the pre-cycle (28% completeness) to 75.38 in cycle I (63% completeness), indicating improved learning outcomes. However, cycle II must be carried out because it does not satisfy the Indicators of Success standards. In cycle II, they rose to 81.72 (84% completion). In addition to encouraging determined development, the TGT with CRT strategy encouraged students’ active participation in the learning process. It offered educational opportunities more in line with the students’ cultural backgrounds. Students’ comprehension of mathematical topics is thereby improved by using the CRT-based TGT learning approach. Keywords: Teams Games Tournament, Culturally Responsive Teaching, mathematical conceptual understanding